PHYSICAL FITNESS ANALYSIS OF THE HIGH-GRADE PRIMARY SCHOOL STUDENTS IN THE DISTRICT OF ACEH BESAR - Putra, Sukardi; KS., Soegiyanto; Sulaiman, Sulaiman (Universitas Negeri Semarang, 2017)
Physical fitness is closely related to the students’ daily health because it is a person's ability to perform activities or work without experiencing significant physical fatigue. Physical fitness is closely related to human activities in conducting physical activities either on purpose or unintentionally. The more the students involve the body to move, the better the level of their physical fitness is. The learners of the high-grade primary schools in the District of Aceh Besar have improved their physical fitness through the implementation of physical education at school and in daily physical activities together within the family and community. However, analysis of the impacts of such physical fitness is still minimal. This study aims to determine the physical fitness level of the high-grade students of the primary schools in the District of Aceh Besar. The method of study was a field measurement test with the Indonesia Physical Fitness Test (IPFT) instrument. The samples in this study were high-grade students of the Primary Schools in Aceh Besar District in 2015 totaling 81 students from three different areas: advanced, developing and underdeveloped. The data were analyzed using descriptive statistics to calculate the mean and percentage. The data analysis resulted in the following conclusions: The average physical fitness of the high-grade students of the primary schools in Aceh Besar District are in the poor category, while the classification is: very good category (2.46%), good category (4.93%), average category (51.85), poor category (32.09%), and very poor category (9.87%). Based on the results, physical activities packaged in physical education should be intensified both at school and outside of school hours and is assessed continually.